Correction: Klemann et al. Quantifying the Resilience of a Healthcare System: Entropy and Network Science Perspectives. Entropy 2024, 26, 21 - Désirée Klemann; Windi Winasti; Fleur Tournois; Helen Mertens; Frits van Merode (Entropy)
In the original publication [...]